The Current Role of Radiotherapy in the Treatment of Small Cell Lung Cancer. Issue 11 (November 2016) - Woolf, D.K.; Slotman, B.J.; Faivre-Finn, C.
Abstract: Radiotherapy has been shown to play a key role in the management of small cell lung cancer. There are well-established data in the literature for the use of concurrent chemoradiotherapy for stage I–III disease, although key questions remain over the timing of radiation, the optimal dose/fractionation and particularly once versus twice daily treatment, the use of elective nodal irradiation and drug combinations. Data for the use of thoracic radiation in stage IV disease, after chemotherapy, have recently become available and are leading to a change in practice. Prophylactic cranial irradiation has been shown to be of use in both stage I–III and stage IV disease, although uncertainties surround its use in the elderly population and the use of brain imaging before treatment. This overview will address the current available evidence and focus on areas for future research.